Pelatihan dan Pembuatan Website pada Pemerintahan dan UMKM Desa Kedawung, Karawang - Aries Suharso; Chaerur Rozikin; Kusnadi Kusnadi; Dewi Ratih Nurcahyani (Universitas Mathla'ul Anwar Banten, 2021)
TRAINING AND WEBSITE DEVELOPMENT AT KEDAWUNG VILLAGE GOVERNMENT AND SMES. Some Kedawung villagers own several UKM (Small and Medium Enterprises) such as Opak business to ginger cultivation. One of the lucrative business opportunities is the high market interest in home-based business products or Small and Medium Enterprises (SMEs). However, the lack of attention and attention by the local government, and the absence of promotional activities carried out by business actors have resulted in some SMEs in Kedawung Village being less developed. The analysis carried out in Kedawung Village includes, analysis of village needs and analysis of village business needs. The research method used in this research is work plan planning, UI design, database design and user flow design and usage procedures. The results of this research are the creation of village websites and UMKM websites, the existence of a good village management information system and the increased skills and abilities of village officials.